SPECIFICS OF PROGRAMMING DYNAMIC SITES WITH BASIC INTERACTIVE OBJECTS - Issakova, Г.О.; Suleimenova, Р.З.; Tanykpayeva, Б.Е.; Yessenbayev, Г.Р.; Tulkibayev, А.Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
It is difficult to imagine the modern Internet without dynamic websites with interactive elements. These elements are various buttons for transitions between individual structural blocks of a Web page, buttons for launching video clips and audio fragments, links that allow you to navigate through the elements of the structure, form elements that expand the boundaries of a single resource. Sites close to those described can be developed using CSS styles or developed under a CMS system. However, it is programming that allows to get a website for a reason. The paper reveals the specifics of programming dynamic sites with basic interactive elements, which allows not only to write a new dynamic site, but also to modernize the old site implemented using HTML without completely rewriting the latter. The main idea is a systematic approach to object-oriented programming using the fundamental capabilities of the JavaScript and HTML programming languages along with CSS elements for formatting site pages, its design, changing the presentation of the site depending on the screen of an electronic device. As a result, the proposed programming features of Web pages make it possible to change the basic approach to creating modern dynamic sites created independently of the proposed CMS systems and significantly expand the capabilities of existing HTML sites.